The Analysis of the Influence of Service Quality, Price, and Promotion on Purchase Decision Maxim Users in Semarang City : Analysis of the Influence of Service Quality, Price, and Promotion on Purchase Decision Maxim Users in Semarang City - Hartanto, Agil Latif; Sutrisno; P, Ratih Hesty Utami (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
The growth of technology and information in the globalization era has accelerated significantly, particularly with the advent of the internet, which has made various activities more efficient. One sector that has been notably impacted is the economy, especially through online ride-hailing services. This study aims to analyze the extent to which service quality, price, and promotion influence the purchase decisions of Maxim online ride-hailing users in Semarang City. A quantitative research method was employed, distributing questionnaires to 200 Maxim users. The results show that service quality and price do not significantly affect purchase decisions, while promotion has a significant influence. Simultaneously, all these variables impact the purchase decisions of Maxim users in Semarang City. These findings suggest that Maxim consumers are more influenced by promotional strategies than by service quality and price factors.